The Potential Application of Magnetic Nanoparticles for Liver Fibrosis Theranostics - Eftekhari, Aziz; Arjmand, Allahveirdy; Asheghvatan, Ayyub; Švajdlenková, Helena; Šauša, Ondrej; Abiyev, Huseyn; Ahmadian, Elham; Smutok, Oleh; Khalilov, Rovshan; Kavetskyy, Taras; Cucchiarini, Magali (Frontiers in Chemistry, 2021)
Liver fibrosis is a major cause of morbidity and mortality worldwide due to chronic liver damage and leading to cirrhosis, liver cancer, and liver failure. To date, there is no effective and specific therapy for patients with hepatic fibrosis. As a result of their various advantages such as biocompatibility, imaging contrast ability, improved tissue penetration, and superparamagnetic properties, magnetic nanoparticles have a great potential for diagnosis and therapy in various liver diseases including fibrosis. In this review, we focus on the molecular mechanisms and important factors for hepatic fibrosis and on potential magnetic nanoparticles-based therapeutics. New strategies for the diagnosis of liver fibrosis are also discussed, with a summary of the challenges and perspectives in the translational application of magnetic nanoparticles from bench to bedside.